2019
DOI: 10.3390/rs11242998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sentinel-3A Wave Height Observations Near the Coast of Southwest England

Abstract: Due to the smaller ground footprint and higher spatial resolution of the Synthetic Aperture Radar (SAR) mode, altimeter observations from the Sentinel-3 satellites are expected to be overall more accurate in coastal areas than conventional nadir altimetry. The performance of Sentinel-3A in the coastal region of southwest England was assessed by comparing SAR mode observations of significant wave height against those of Pseudo Low Resolution Mode (PLRM). Sentinel-3A observations were evaluated against in-situ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…If the error Err buoy exceeds 1 m for buoy i, this buoy is considered as unreliable and its records are discarded. Given that the majority of the buoys match well with the various altimeter estimates, a median error of this magnitude implies a poorly calibrated buoy or else one that is too far from the altimeter track as to not provide representative ground truth values (see [26]).…”
Section: Comparison Against In-situ Datamentioning
confidence: 99%
See 2 more Smart Citations
“…If the error Err buoy exceeds 1 m for buoy i, this buoy is considered as unreliable and its records are discarded. Given that the majority of the buoys match well with the various altimeter estimates, a median error of this magnitude implies a poorly calibrated buoy or else one that is too far from the altimeter track as to not provide representative ground truth values (see [26]).…”
Section: Comparison Against In-situ Datamentioning
confidence: 99%
“…Nencioli and Quartly [26] developed a methodology to use model data to help inform the choice of suitable match-ups, showing that some locations 20 km apart could be poorly correlated, whereas other locations much further away but with good exposure would give equivalent measures for validation purposes. In particular, it was noted that a small number of the buoys selected from our validation exercise were in well sheltered locations unrepresentative of those conditions further offshore.…”
Section: Round Robin Assessment Retrospectivementioning
confidence: 99%
See 1 more Smart Citation
“…These values were determined by Monaldo [29] based on examination and auto-correlation analysis of altimeters and buoys, respectively. Nencioli and Quartly [30] showed that aspects of the coastline morphology and orientation to the prevailing waves can be important in the coastal zone, and this is an issue that we address later. In this paper, we re-use the match-up database provided for the Round Robin paper [5], so the information is only recapped here.…”
Section: Data Match-upmentioning
confidence: 94%
“…The uncertainty in estimates due to fading noise typically increases with SWH, but is much more pronounced in the near-shore region (Figure 15b potential for improved SWH accuracy near land (Nencioli and Quartly, 2019) and reduced sensitivity to fading noise through "multi-looking" (Raney, 1998).…”
Section: Assessment and Implementation Of New Retracking Algorithmsmentioning
confidence: 99%